Market information and access to structured markets by small farmers and traders: Evidence from an action research experiment in central Malawi - Ochieng, Dennis O.; Botha, Rosemary; Baulch, Bob (International Food Policy Research Institute, 2020)
Small farmers and traders often lack the market information they need to earn the most from their crop sales. This paper analyzes the effects of an action research experiment in central Malawi, in which four groups of smallholder farmers were provided with maize and soybean price information from a local commodity exchange during the 2019 marketing season, while four other groups of smallholder farmers did not receive this information. Using data from a panel survey of 399 farmers and 78 traders conducted before and after the main marketing season and using kernel propensity score matching approach to account for possible differences between the treated and non-treated farmers, we estimate the effects of the intervention on a number of outcome indicators. A before versus after analysis was also employed to evaluate changes in traders’ marketing outcomes. We find positive but statistically insignificant effects on maize and soybean selling prices, sales through structured markets and levels of commercialization after the intervention. We also find a negative and statistically significant effect on the quantity of maize sold by farmers, suggesting paradoxically that providing farmers with price information reduced their sales volumes. The proportion of traders aware of structured markets and their share of sales through structured markets also increased significantly after the intervention. The quantity of maize sold by traders as well as the selling prices for maize and soy-bean also increased significantly, although this may be due to factors other than the intervention. The study concludes that provision of price information alone is not enough to facilitate small farmers’ and traders’ use of structured markets. Greater effort is needed to sensitize farmers and traders on the quality and quantity requirements as well as the operations of structured markets.